The study on thermal performance and daylighting of transparent concrete / Karthikgheyan Vasudevan, Hazril Sherney Basher and Mohd Hafizal Mohd Isa - Vasudevan, Karthikgheyan; Basher, Hazril Sherney; Mohd Isa, Mohd Hafizal (2022)
Concrete is the most used building material in the world. Modern technology studies and research developments have enhanced the quality and innovation of concrete. Transparent concrete is concrete that has light-transmitting properties which transmit light through the optical fibre. Optical fibres are reinforced in the conventional concrete mixture from one face to another face, which allows direct sunlight to transmit through it. Daylighting factor is one of the fundamental qualities of the energy efficiency of a building. The thermal performance is also crucial to providing comfort to the building occupants. The literature studies cover the light transmittance and thermal performance of transparent concrete. Selected literature studies are reviewed based on the related topic, Asian countries, and countries with a similar climate to Malaysia. This research applies the quantitative method which was focused on the experimental study of transparent concrete. The overall result indicates improvement on light transmission and thermal performance as the plastic optical fibre increased compared to conventional concrete. The total average surface temperature of transparent concrete shows a difference of 0.989°C lower than conventional concrete. This experiment's significant contribution is that using more plastic fibre optic reduces thermal conductivity and heat gain while allowing for greater daylighting. Finally, transparent concrete shows effectiveness in light transmission and thermal resistance which can contribute to building industry on green building and sustainable design. However, further studies on thermal performance with a longer duration are required to analyse the thermal heat loss.